Nanomedicine: A Review - Varsha Gangwani, Bharat Chouhan (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
The clinical use of nanotechnology is called nanomedicine. Nanomedicine combines organic machines with biological devices, molecular nanotechnology, nano-electronic biosensors, and even potential future uses. Depending on the range of its uses, nanomedicine and nanoparticles have different physical, chemical, and mechanical characteristics.